Role of Executive Functions in Lexical Selection - Shaji, Sneha Roslyn; Jacob, Hima; Shivaiah, Chandana; P., Abhishek B. (Journal of Health and Allied Sciences NU, 2023)
Objectives This article determines the number of correct responses under confrontation naming, producing category coordinates, superordinates, and features associated with the target.Materials and Methods Thirty participants in the age range of 18 to 30 years served as participants. The study was carried out in Malayalam, the native language of the participants. A conditioned naming task was administered to the participants.Statistical Analysis Within-group analysis was carried out using Friedman's test.Results It was found that the participants erred more in naming category coordinates, derivatives, and superordinates.Conclusion The amount of cognitive control varied for each of these conditional naming tasks, and with increasing complexity in cognitive control, scores on conditional naming tasks also differed, showing the relationship between these two aspects.
Keywords: executive control; response inhibition; cognitive flexibility; conditional naming